2018
DOI: 10.1103/physrevb.97.020506
|View full text |Cite
|
Sign up to set email alerts
|

Coupled dipole oscillations of a mass-imbalanced Bose-Fermi superfluid mixture

Abstract: Recent experimental realizations of superfluid mixtures of Bose and Fermi quantum gases provide a unique platform for exploring diverse superfluid phenomena. We study dipole oscillations of a double superfluid in a cigar-shaped optical dipole trap, consisting of 41 K and 6 Li atoms with a large mass imbalance, where the oscillations of the bosonic and fermionic components are coupled via the Bose-Fermi interaction. In our high-precision measurements, the frequencies of both components are observed to be shifte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 36 publications
(75 reference statements)
1
31
0
Order By: Relevance
“…It is also observed that the frequency of the Bose superfluid is downshifted (upshifted) in the axial (radial) direction, while the frequencies of the Fermi superfliud are downshifted in the both directions. The variation of the frequency shift shows a nonmonotonic behavior around the BCS side [35], differently from a monotonic increase in the 7 Li- 6 Li superfluid mixture.…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…It is also observed that the frequency of the Bose superfluid is downshifted (upshifted) in the axial (radial) direction, while the frequencies of the Fermi superfliud are downshifted in the both directions. The variation of the frequency shift shows a nonmonotonic behavior around the BCS side [35], differently from a monotonic increase in the 7 Li- 6 Li superfluid mixture.…”
Section: Introductionmentioning
confidence: 73%
“…In the ENS experiment of 7 Li- 6 Li superfluid mixture [1], the frequency of the Bose superfluid oscillating along the axial direction is found to be downshifted, and the value of the downshift increases monotonically from the BCS side to BEC side. Subsequently, the USTC group studied both axial and radial dipole oscillations in the 41 K- 6 Li superfluid mixture which has a large mass imbalance [6]. The frequency shifts of the Bose and Fermi superfluids are both measured in high precision, and the frequency shift of the Fermi superfluid is showed to be much smaller than the bosonic counterpart.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations